In Vitro Disease Models for Understanding Psoriasis and Atopic Dermatitis - Sarama, Roudin; Matharu, Priya K.; Abduldaiem, Yousef; Corrêa, Mab P. [UNESP]; Gil, Cristiane D.; Greco, Karin V. (Frontiers, 2022)
Psoriasis (PS) and Atopic Dermatitis (AD) are two of the most prevalent inflammatory skin diseases. Dysregulations in the immune response are believed to play a crucial role in the pathogenesis of these conditions. Various parallels can be drawn between the two disorders, as they are both genetically mediated, and characterised by dry, scaly skin caused by abnormal proliferation of epidermal keratinocytes. The use of in vitro disease models has become an increasingly popular method to study PS and AD due to the high reproducibility and accuracy in recapitulating the pathogenesis of these conditions. However, due to the extensive range of in vitro models available and the majority of these being at early stages of production, areas of development are needed. This review summarises the key features of PS and AD, the different types of in vitro models available to study their pathophysiology and evaluating their efficacy in addition to discussing future research opportunities.
Keywords: 3D models; atopic dermatitis (AD); fibroblast; in vitro; keratinocyte; psoriais